IMPLEMENTATION OF A WEB-BASED NETWORK PERFORMANCE MONITORING SYSTEM USING THE QUALITY OF SERVICE (QOS) METHOD ON MIKROTIK ROUTER INFRASTRUCTURE - Alingga Rayhan Pratama; Budi Sutomo (Djtechno: Jurnal Teknologi Informasi, 2026)
This study implements a web-based network performance monitoring system integrated with a MikroTik router using Quality of Service (QoS) parameters. The system uses PHP, MySQL, and the RouterOS API to acquire interface traffic and ping results. The measured parameters include throughput, latency, jitter, and packet loss. Measurement records are stored in a database and displayed as current and historical monitoring data. The test results show that the system can read router resources, calculate QoS values, display real-time traffic, and help administrators monitor network quality in a centralized manner.